On the quantitative criteria of subspecies in insects. Case study of Entomoscelis adonidis (Coleoptera: Chrysomelidae) in European Russia and the Caucasus - Bieńkowski, Andrzej O.; Orlova-Bienkowskaja, Marina J. (Zootaxa, 2023)
Many insect subspecies are described without a statistical assessment of differences. In this work, an attempt is made to statistically process the morphological differences of some recently described subspecies. In this regard, a taxonomic review of Entomoscelis adonidis (Pallas, 1771) (Coleoptera, Chrysomelidae) and related taxa described from European Russia and the Caucasus is presented. Statistical processing of numerous materials (782 specimens) from type localities of the nominal taxa adonidis, spuria Jacobson, 1896, caucasica Kippenberg, 2020, and bashkiriae Kippenberg, 2020, and their environs showed the presence of geographical variability in several characters, which, however, does not reach the level of species or subspecies. For subspecies, the classic “75 %” rule is applied. Therefore, all these specimens are considered to belong to the same species and subspecies. For nomenclature stability and to clarify the taxonomic position of closely related taxa, the neotype of Chrysomela adonidis Pallas is designated from the type locality; the neotype is in accordance with the currently used interpretation of E. adonidis adonidis. Besides that, the lectotype of Entomoscelis adonidis var. spuria Jacobson is designated. The paratypes of E. adonidis caucasica Kippenberg and E. dorsalis bashkiriae Kippenberg were studied. The following new synonyms are proposed: E. adonidis adonidis (Pallas, 1771) = E. adonidis caucasica Kippenberg, 2020 (syn. nov.) = E. dorsalis bashkiriae Kippenberg, 2020 (syn. nov.). The status of E. adonidis var. spuria Jacobson, 1896 as a junior synonym of E. adonidis adonidis is confirmed. The endophallus, particularly, flagellum of E. adonidis was studied for the first time. Several Brassicaceae species, namely Berteroa incana, Barbarea vulgaris, Sisymbrium officinale, Capsella bursa-pastoris, and Thlaspi arvense, as well as Adonis vernalis (Ranunculaceae) are confirmed as host plants of the adults of E. adonidis in cages.